2013
DOI: 10.1007/s00277-013-1953-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune status of Fanconi anemia patients: decrease in T CD8 and CD56dim CD16+ NK lymphocytes

Abstract: Fanconi anemia (FA), a rare genetic disease in which patients' life is compromised mainly by hematological abnormalities and cancer prone, seems to be affected by subtle immune cell irregularities. Knowing that FA presents developmental abnormalities and, based on recent reports, suggesting that natural killer (NK) CD56(dim) and NK CD56(bright) correspond to sequential differentiation pathways, we investigated if there were changes on the total number of NK cells and subsets as well as on T CD4 and T CD8 lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Justo et al. also observed a decrease in NK CD56dimCD16 + and CD8 + T cells in FA compared to non‐FA controls . Giri et al.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Justo et al. also observed a decrease in NK CD56dimCD16 + and CD8 + T cells in FA compared to non‐FA controls . Giri et al.…”
Section: Introductionmentioning
confidence: 91%
“…The FA phenotype is the result of mutations in one of 20 known genes that function in the DNA interstrand cross‐link repair pathway, leading to aberrant correction of DNA breaks. Heterogeneous abnormalities in the immune function of individuals with FA have been reported in several studies . We have previously reported in a small series that individuals with FA have decreased natural killer (NK) cells and NK function, perforin and granzyme levels, CD19 + B cells, cytotoxic lymphocyte (CTL) function, and tetanus responses .…”
Section: Introductionmentioning
confidence: 97%
“…Natural killer (NK) cell numbers and function have been reported to be decreased in some FA patients and this was associated with impairment in the differentiation process of the NK cells subsets [85, 86]. Myers et al showed perforin and granzyme reduced content in NK cells from children with FA as compared to controls [87].…”
Section: Natural Killer Cells In Periodontitismentioning
confidence: 99%
“…, 2008; Pagano et al. , 2003, 2012; Zanier et al , 2004; Myers et al , 2011; Justo et al , 2014; Parodi et al , 2015; Sumpter et al , 2016), the well-established “canonical” function of the proteins is to work along a “linear” pathway that addresses replication stresses, assuring the transmission of a stable genome from one cell to the daughters and acting both during DNA replication to cope with stalled replication forks and in G2 and M phases to resolve underreplicated regions before cell division (Ceccaldi et al , 2016; Lopez-Martinez et al , 2016; Michl et al , 2016). How the other, noncanonical functions of the FANC proteins that are involved in cytokine production/response, inflammation (Rosselli et al , 1994; Fagerlie et al , 2001; Pang et al , 2001; Zanier et al , 2004; Briot et al , 2008), mitophagy Sumpter et al , 2016), and oxygen free radical metabolism (Joenje et al , 1981; Pagano et al , 2003; Pagano et al , 2012) as well as the subtle defects in immunity (Myers et al.…”
Section: Introductionmentioning
confidence: 99%
“…How the other, noncanonical functions of the FANC proteins that are involved in cytokine production/response, inflammation (Rosselli et al , 1994; Fagerlie et al , 2001; Pang et al , 2001; Zanier et al , 2004; Briot et al , 2008), mitophagy Sumpter et al , 2016), and oxygen free radical metabolism (Joenje et al , 1981; Pagano et al , 2003; Pagano et al , 2012) as well as the subtle defects in immunity (Myers et al. , 2011; Justo et al. , 2014; Nguyen et al.…”
Section: Introductionmentioning
confidence: 99%